ANALISIS RASIO KEUANGAN TERHADAP RETURN SAHAM SEKTORFOOD AND BEVERAGE - Lydia Sumiyati (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2016)
The objective of this study is toexamine the influence of Net Profit Margin, Current Ratio,Debt to Equity Ratio, Inventory Turnover and Price Earning Ratio against to stock return on themanufactur companies of Food and Beverages Sectors periode 2010-2014 partially. The populationin this research were the companies on Food and Beverages Sectors was listed in Indonesia StockExchange periode 2010-2014 and for the sampel were 6 companies by purposive samplingmethode.Independent variabel in this research were Net Profit Margin, Current Ratio, Debt to EquityRatio, Inventory Turnover and Price Earning Ratio. Dependent variabel were stock return. Theanalysis technique used multiple regression analysis and hypotheses test used T-test. It also madethe classic assumption test covering multicollinierity test, autocorrelation test, normally test, andheteroskedasticity test.In this research, partial NPM, CR, DER, ITO, and PER have not significant influence on thefood and baverages company’s stock return. Significance value of NPM 0,142 with α = 0,05 wheresig (0,142) > α (0,05), value of CR 0,851 with α = 0,05 where sig (0,851) > α (0,05), value of DER0,916 with α = 0,05 where sig (0,916) > α (0,05), value of ITO 0,586 with α = 0,05 where sig (0,586)> α (0,05), and value of PER 0,767 with α = 0,05 where sig (0,767) > α (0,05).